2021
DOI: 10.3390/plants10061222
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Gains in Maize Kernels Are Dependent on Their Nitrogen Accumulation Rates and Duration during Grain Filling

Abstract: Progressive N assimilation by maize kernels may constrain dry matter (DM) accumulation and final kernel weights (KW). We sought to better understand whole-plant and kernel N mechanisms associated with incremental DM and N accumulation patterns in kernels during grain fill. Maize was grown with multiple fertilizer N rates and N timings or plant densities to achieve a wide N availability gradient. Whole-plant DM and N sampling enabled determination of apparent N nutrition sufficiency at flowering (NNIR1) and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 61 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Higher N supply, regardless of application timing or plant density, increased grain-fill duration and, more inconsistently, effective grain-filling rate. Kernels accumulated dry matter and N for similar durations (Olmedo Pico and Vyn, 2021). Grain yield is clear by the product of grain number and kernel weight.…”
Section: Discussionmentioning
confidence: 92%
“…Higher N supply, regardless of application timing or plant density, increased grain-fill duration and, more inconsistently, effective grain-filling rate. Kernels accumulated dry matter and N for similar durations (Olmedo Pico and Vyn, 2021). Grain yield is clear by the product of grain number and kernel weight.…”
Section: Discussionmentioning
confidence: 92%
“…The grouting process is susceptible to environmental factors such as water content, soil nutrient status, environmental temperature, and nitrogen application rate [44,48]. The study of Lía B [49] and Gasura et al [50] showed that the grain-filling duration significantly correlated with the grain yield of maize; the grain yield increased dramatically with the grain-filling rate and grain-filling duration. In this study, the duration of the maize gradual increase period under traditional plastic film or degradable film mulching was the shortest under a nitrogen application rate of 320 kg•ha −1 , followed by no nitrogen application.…”
Section: Effects Of Plastic-film Mulching and Nitrogen Application On...mentioning
confidence: 99%
“…Water is the main limiting factor for maize production, and maize responds differently to water stress at different growth stages (Gheysari et al., 2021; Rasool et al., 2020). Moreover, the N accumulation rate and grain‐filling duration were considered as the factors affecting the proliferation of maize grain and dry matter (DM) (Olmedo Pico & Vyn, 2021). Guangxi is located in the subtropical zone with a typical monsoon climatic condition.…”
Section: Introductionmentioning
confidence: 99%